Does the Path From Cigarette Smoking to Suicide Death Go Through the Hospital? A Causal Mediation Analysis in a National Canadian Sample - lloyd Balbuena; Fredrik Åhs; Evyn Peters; Ana Mendes-Silva; Doug Speed (Tobacco Use Insights)
Background Although many epidemiological studies show an association of cigarette smoking with suicide the path to the latter is not well understood. Objective Using causal inference methodology with observational data, to examine if smoking leads indirectly to suicide through mental health hospitalization. Design The study used 11 waves of a cross-sectional national health survey that was linked with hospitalization and death registers. Methods The data came from Canadian Community Health Survey respondents (n = 723 665) between the years 2000 and 2014. These respondents agreed to link their data with hospitalization and death registers and were followed for an average of 9.18 (SD: 4.42; range: 3 to 17) years. Mediation models, one each for men and women, were created in which lifetime daily smoking was the exposure, mental health hospitalization was the mediator, and death by suicide was the outcome, adjusting for 11 covariates reported at survey participation. Results In both men and women, the direct effect of daily smoking was larger than the indirect effect through hospitalization for mental conditions. The direct effect of smoking was 1.76 (95% CI: 1.47-2.10) for men and 2.60 (95% CI: 1.90-3.57) for women. The indirect effect through mental health hospitalization was 1.07 (95% CI: 1.05-1.09) for men and 1.04 (95% CI: 0.99-1.09) for women. Conclusion A relatively smaller proportion of the daily smoking-suicide association is transmitted indirectly through mental health hospitalizations compared to a direct effect. Suicide interventions focusing on people hospitalized for mental disorders may miss many suicidal people, so primary prevention and secondary prevention of smoking are crucial.